Sensitive determination of nitrophenol isomers by reverse-phase high-performance liquid chromatography in conjunction with liquid–liquid extraction. Issue 11 (2nd September 2017) - Boddu, Veera; Kim, Sanghoon; Adkins, Jason; Weimer, Ellyn; Paul, Tias; Damavarapu, Reddy
ABSTRACT: A method for the highly sensitive determination of 2-, 3- and 4-nitrophenols was developed using reverse-phase high-performance liquid chromatography (RP-HPLC) with a UV photodiode array detector. Using a reverse-phase column and 40% aqueous acetonitrile as an eluent (i.e. isocratic elution), the integrated peak area of detector output was linear up to 300 mg/L and the detection limit was 150 µg/L. The sensitivity of this detection method was improved by pretreating the sample solutions with a solvent extraction procedure that makes use of the high partition coefficient of ethyl acetate (EA)/water system. To find an optimum condition for the extraction procedure, this process was simulated by plotting the concentration of nitrophenol extracted in organic solvent against the volume multiplication factor at various partition coefficient of solute. This simulation demonstrated that EA is a superior extractant to other organic solvents. With the newly developed method, the detection limit was extended to 0.3 µg/L. This method offers fast, reliable and more sensitive determination of nitrophenol isomers than any other HPLC method.